EVACUATION ROUTE MAPPING AGAINST SLAMET VOLCANO DISASTER AT GUNUNGSARI VILLAGE, PULOSARI SUB DISTRICT, PEMALANG DISTRICT - Misdiyanto Misdiyanto; Djoko Legono; Subagyo Pramumijoyo (Department of Civil and Environmental Engineering, Faculty of Engineering, UGM, 2014)
Villages inside the hazard zone of Slamet Volcano should have an evacuation map, as an anticipation and guidance to guide people evacuate when volcanic activity on the area arise to dangerous level. The experience which occurred at 2009 and 2010 indicate the necessity of the development of evacuation map for 7 villages inside the hazard zone in the Pemalang residential district, such as village of Gunung Sari. The main purpose of the developing an evacuation map is to make the village of Gunung sari becoming more vigilant to anticipate the danger of Slamet Mount eruption. Qualitative methods were used in this study, by handing out preliminary questionnaire to investigate the characteristic of the residents. The development of evacuation map also relies on the participation of the residents, then the resulted map were evaluated by assessing how far people can understand and comprehend any information provided on the map. The result of the investigation shows that Gunungsari’s resident wants an evacuation map, shown by high enthusiasm on the questions of the necessity of an evacuation map and disaster preparedness team that is equal to 97% of the residents on Dusun Sipendil, 83% on dusun Sibedil, 67% on Dusun Silegok, and 63% on Dusun Krajan. The residents also understand and comprehend the information provided on the map nicely, especially about the timing and rendezvous location for the evacuation. It is indicated by high proportion of residents that answer the questions asked accurately, which is 100% on Dusun Sipendil, 97% on Dusun Sibedil, and 80% for both Dusun Silegok and Dusun Krajan.Keywords: disaster prone area, evacuation map, society characteristic